A randomized controlled trial for response of microbiome network to exercise and diet intervention in patients with nonalcoholic fatty liver disease - Cheng, Runtan; Wang, Lu; Le, Shenglong; Yang, Yifan; Zhao, Can; Zhang, Xiangqi; Yang, Xin; Xu, Ting; Xu, Leiting; Wiklund, Petri; Ge, Jun; Lu, Dajiang; et al. (Nature communications, 2022)
Exercise and diet are treatments for nonalcoholic fatty liver disease (NAFLD) and prediabetes, however, how exercise and diet interventions impact gut microbiota in patients is incompletely understood. We previously reported a 8.6-month, four-arm (Aerobic exercise, n = 29; Diet, n = 28; Aerobic exercise + Diet, n = 29; No intervention, n = 29) randomized, singe blinded (for researchers), and controlled intervention in patients with NAFLD and prediabetes to assess the effect of interventions on the primary outcomes of liver fat content and glucose metabolism. Here we report the third primary outcome of the trial—gut microbiota composition—in participants who completed the trial (22 in Aerobic exercise, 22 in Diet, 23 in Aerobic exercise + Diet, 18 in No Intervention). We show that combined aerobic exercise and diet intervention are associated with diversified and stabilized keystone taxa, while exercise and diet interventions alone increase network connectivity and robustness between taxa. No adverse effects were observed with the interventions. In addition, in exploratory ad-hoc analyses we find that not all subjects responded to the intervention in a similar manner, when using differentially altered gut microbe amplicon sequence variants abundance to classify the responders and low/non-responders. A personalized gut microbial network at baseline could predict the individual responses in liver fat to exercise intervention. Our findings suggest an avenue for developing personalized intervention strategies for treatment of NAFLD based on host-gut microbiome ecosystem interactions, however, future studies with large sample size are needed to validate these discoveries. The Trial Registration Number is ISRCTN 42622771. Exercise and diet interventions are treatments for nonalcoholic fatty liver disease (NAFLD). Here the authors report that in randomized, controlled trial in patients with NAFLD exercise and diet intervention were associated with diversified gut microbiome keystone taxa. Exploratory analysis suggests gut microbial network may be used to predict the individual liver fat response to exercise intervention, if validated in future studies.